ONLINE RESEARCH FOR DEEPER LEARNING IN EFL CLASSROOMS - Susan Bremner (PUPIL: International Journal of Teaching, Education and Learning, 2026)
Technology continues to expand the boundaries of language learning, offering opportunities for communication, collaboration, and engagement beyond the traditional classroom. When strategically integrated, online research can serve as a powerful tool for independent learning, enabling students to interact meaningfully with content and demonstrate understanding in personalized ways. However, both educators and learners may find the extensive access to resources challenging to navigate and potentially distracting. Furthermore, the abundance of information, along with the growing prevalence of generative AI tools, can be overwhelming for learners and result in passive consumption and reproduction when active learning and demonstration of knowledge and linguistic skills is desired. To address these challenges, this presentation explores how guided independent research can provide structured yet flexible pathways for English as a Foreign Language (EFL) students to create their own content. Drawing on case studies from Japanese EFL classrooms, the presentation will illustrate the implementation of guided research tasks that incorporate audio-visual learning tools, Content and Language Integrated Learning, and Project-Based Learning. This approach creates a supportive and stimulating environment for learners to engage with online materials while promoting student-centred problem-solving and the development of critical thinking skills. The presentation will highlight both the pedagogical benefits and practical challenges of implementation, with a focus on evaluating learner outcomes, and advocate for the thoughtful integration of technology and research-based tasks to promote deeper learning and responsible digital practices in EFL education.